Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1, 54 : x - 1 = 5
54 : x = 5+1 = 6
x = 54 : 6 = 9
2, 42 : x + 0 = 8
x = 42 : 8 = 21/4
3, 24 : x - 8 = 0
24 : x = 0 + 8 = 8
x = 24 : 8 = 3
Tk mk nha
\(\frac{3}{4}\times\frac{4}{7}+\frac{3}{7}\times\frac{3}{2}\)
\(=\frac{3}{7}+\frac{9}{14}=\frac{15}{14}\)
\(X+\frac{31}{2}+X=24\frac{1}{4}\)
\(\Rightarrow2x+\frac{31}{2}=24\frac{1}{4}\)
\(\Rightarrow2x=24\frac{1}{4}-\frac{31}{2}\)
\(\Rightarrow2x=\frac{35}{4}\)
\(\Rightarrow x=\frac{35}{4}:2=\frac{35}{8}\)
\(x-3\frac{1}{2}+x=24\frac{1}{4}\)
\(x-\frac{7}{2}+x=\frac{97}{4}\)
\(x-\frac{7}{2}=\frac{97}{4}-x\)
\(x+x=\frac{7}{2}+\frac{97}{4}\)
\(x+x=\frac{111}{4}\)
\(x\cdot2=\frac{111}{4}\)
\(x=\frac{111}{4}:2\)
\(x=\frac{111}{8}\)
\(x=13,875\)
\(x+3\frac{1}{2}+x=24\frac{1}{4}\)
\(2x+\frac{7}{2}=\frac{97}{6}\)
\(2x=\frac{38}{3}\)
\(x=\frac{38}{3}:2\)
\(x=\frac{19}{3}\)
\(x+3\frac{1}{2}+x=24\frac{1}{4}\)
=> \(x+\frac{7}{2}+x=\frac{97}{4}\)
=> \(2\times x+\frac{7}{2}=\frac{97}{4}\)
=> \(2\times x=\frac{97}{4}-\frac{7}{2}=\frac{83}{4}\)
=> \(x=\frac{83}{4}:2=\frac{83}{4}\cdot\frac{1}{2}=\frac{83}{8}\)
Trả lời :
\(x+3\frac{1}{4}+x=24\frac{1}{4}\)
\(x+\frac{13}{4}+x=\frac{97}{4}\)
\(x\text{ x 2 }+\frac{13}{4}=\frac{97}{4}\)
\(x\text{ x 2 }=\frac{97}{4}-\frac{13}{4}\)
\(x\text{ x 2 }=\frac{84}{4}=21\)
\(x=21:2\)
\(x=10,5\)
\(x+3\frac{1}{4}+x=24\frac{1}{4}\)
\(\Rightarrow2x+\frac{13}{4}=\frac{97}{4}\)
\(\Rightarrow2x=21\)
\(\Rightarrow x=\frac{21}{2}\)
x + \(3\frac{1}{2}\)+ x = \(24\frac{1}{4}\)
x + \(\frac{7}{2}\)+ x = \(\frac{97}{4}\)
x + x = \(\frac{97}{4}-\frac{7}{2}\)
x X 2 = \(\frac{83}{4}\)
x = \(\frac{83}{4}:2\)
x = \(\frac{83}{8}\)
a) \(x+1,23\div3=1,845\) c) Không rõ
\(x+0,41=1,845\)
\(x=1,845-0,41\)
\(x=1,435\)
b) \(x\times\frac{1}{4}+x\times\frac{1}{5}+x\times2=19,6\) d) \(x+3\frac{1}{2}+20=24\frac{1}{4}\)
\(x\times\left(\frac{1}{4}+\frac{1}{5}+2\right)=19,6\) \(x+\frac{7}{2}+20=\frac{97}{4}\)
\(x\times\frac{49}{20}=19,6\) \(x+\frac{47}{2}=\frac{97}{4}\)
\(x=19,6\div\frac{49}{20}\) \(x=\frac{97}{4}\div\frac{47}{2}\)
\(x=8\) \(x=\frac{97}{94}\)
x + 3 1/2 + x = 24 1/4
2x + 7/2 = 97/4
2x = 97/4 - 7/2
2x = 97/4 - 14/4
2x = 83/4
x = 83/4 : 2
x = 83/4 x 1/2 = 83/8
Vậy x = 83/8
x + 3 1/2 + x = 24 1/4
2x + 7/2 = 97/4
2x = 97/4 - 7/2
2x = 97/4 - 14/4
2x = 83/4
x = 83/4 : 2
x = 83/4 x 1/2 = 83/8
Vậy x = 83/8